Analisa Pengaruh Pendidikan dan Motivasi Kerja Terhadap Perencanaan Karier Berbasis Forecasting dan Scenario Planning - Sunjayani, Dinar Novandia; Saputri, Tira Maulidya; Matalin, Jansend; Supratikta, Hadi (Universitas Pamulang, 2025)
This study explores the influence of education and work motivation on career planning based on forecasting and scenario planning in the context of human resource management. Utilizing a library research method, this literature review draws on various academic sources to evaluate the interplay of education, motivation, and career planning. The findings indicate that education significantly enhances career planning by improving knowledge and skills, while motivation drives individuals to achieve career goals effectively. Additionally, forecasting and scenario planning are identified as valuable tools for designing adaptive career strategies, aligning with organizational needs and future uncertainties. The study underscores the importance of integrating education, motivation, and predictive approaches in fostering effective human resource management.